2021
DOI: 10.7160/aol.2021.130306
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of Using Social Networks as Tools for Integration of Czech Rural Areas - Survey 2021

Abstract: This paper deals with the use of social networks in agricultural enterprises and focuses mainly on their role and share in increasing the competitiveness of agricultural enterprises in the market. Primary data were obtained from an extensive survey of the development of information and communication technologies in agricultural enterprises, which was conducted in the first quarter of 2021 throughout the Czech Republic (“Survey 2021”). The research was primarily focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Kánská et al (2021) investigated the spatial analysis of data on agricultural properties through digital technologies and found that their use promotes the competitiveness of rural properties, thus favoring their growth and economic development. The agribusiness scenario shows that the increase in food productivity is directly bound to the development of agro-industrial production chains and the use of precision agriculture techniques -in agreement with Cima et al (2021a).Čechura et al (2021) evaluated agriculturalproductivity in the Theca Republic by considering spatial analysis.…”
mentioning
confidence: 99%
“…Kánská et al (2021) investigated the spatial analysis of data on agricultural properties through digital technologies and found that their use promotes the competitiveness of rural properties, thus favoring their growth and economic development. The agribusiness scenario shows that the increase in food productivity is directly bound to the development of agro-industrial production chains and the use of precision agriculture techniques -in agreement with Cima et al (2021a).Čechura et al (2021) evaluated agriculturalproductivity in the Theca Republic by considering spatial analysis.…”
mentioning
confidence: 99%
“…Kánská et al (2021) investigated the spatial analysis of data on agricultural properties through digital technologies and found that their use promotes the competitiveness of rural properties, thus favoring their growth and economic development. The agribusiness scenario shows that the increase in food productivity is directly bound to the development of agro-industrial production chains and the use of precision agriculture techniques -in agreement with Cima et al (2021a).Čechura et al (2021) evaluated agriculturalproductivity in the Theca Republic by considering spatial analysis.…”
mentioning
confidence: 99%
“…Digital Innovation Hubs have to guarantee access of local businesses and public authorities to the newest digital technologies and provide training in digital skills. It needs to support specialization of the regions, in line with their regional Smart Specialization Strategies as a set of priority areas for public investment, corresponding to regional competitive advantages(Miörner et al, 2019;Jarolimek et al, 2009;Kánská et al, 2021). To support regional policies and regional businesses is one of the key priorities on PoliRural projects, where an important part was to develop and test utilization of DIHs in regional context(Ulman et al, 2020).Various web map platforms, with potential to support DIHs are available on the scene with a wide range of features, target user groups and maturity level.Provision of web GIS functionality and content can be provided by the large set of open sourced or open license-based solutions like examples mentioned in Table 1.…”
mentioning
confidence: 99%